Transforming the Nursing Workforce in the United States: The Value of Baccalaureate Preparation in Nursing - Cooney Miner, Dianne (Nursing in the 21st Century, 2012)
TRANSFORMING THE NURSING WORKFORCE IN THE UNITED STATES: THE VALUE OF BACCALAUREATE PREPARATION IN NURSING As part of the US dialogue on the nurse of the future, the Institute of Medicine (IOM), one of four US National Academies, released a 2012 report entitled The Future of Nursing: Leading Change, Advancing Health. This report calls for the transformation of US nursing education with a goal of preparing graduates to provide high quality patient care in the roles of provider of care, designer/manager/coordinator of care and as member of a profession. Baccalaureate nursing education (BSN) is the recognized vehicle for this transformation and in recognition of the critical importance of a BSN preparation, the IOM recommends that the US nursing workforce should be at least 80% BSN prepared by 2020. This call for reform from US leadership in nursing, higher education and health policy is strengthened by numerous studies that demonstrated the relationship between higher levels of nursing education and improved patient outcomes. While research continues to identify the differences in outcomes that a baccalaureate prepared nursing workforce can achieve, the American Association of Colleges of Nursing’s model for baccalaureate nursing education discussed in this paper, is the framework for the practice focused outcomes and the knowledge and skills responsible for these achievements.